Transforming noun phrase structure form into rules to detect compound nouns in Malay sentences - Abdul Rahman, Suhaimi; Omar, Nazlia (Universiti Utara Malaysia Press, 2012)
This paper addresses the process of transforming the noun phrase structure form into a list of rules to detect compound noun words in Malay sentences.Rules are collection of word syntax that are derived from a specific resource (as defined in our study).Comprehension of the concept rule used in a system is important (i.e. using rules to find a list of compound nouns that may exist in a sentence).The noun phrase frame structure is a form that contains a list of noun modifier categories.The list of noun modifier categories is then divided into several sub-categories such as numeral, numeral classifier, appellation, etc. All categories are arranged in sequence based on correct grammar.The noun phrase frame structure is then used to analyse the sentence.The words in the sentence will be arranged according to their suitable noun modifier category as defined by the noun phrase frame structure.In terms of data requirements, we will only focus on examples of sentences that combine two noun phrases.